Phase decomposition in a nanocrystalline CrCoNi alloy. (November 2020) - Li, Y.J.; Kostka, A.; Savan, A.; Ludwig, A.
Graphical abstract: Abstract: Phase stability of a nanocrystalline CrCoNi alloy is investigated using the combinatorial processing platform approach, which enables synthesis, processing and direct atomic-scale characterizations of alloys by atom probe tomography and transmission electron microscopy. Phase decomposition with formation of CoNi-rich phase occurs faster in the smaller (10 nm) grain-sized region than the larger one (20 nm), both being present in the same sample. Chemical analyses indicate that diffusion of Co and Cr plays an important role in phase decomposition. Comparison of phase stability between CrMnFeCoNi and CrCoNi implies that elemental segregation may promote phase decomposition by providing an additional chemical driving force for it.